Estrogen Induces Metastatic Potential of Papillary Thyroid Cancer Cells through Estrogen Receptor α and β - Wenwu Dong; Hao Zhang; Jing Li; Haixia Guan; Liang He; Zhihong Wang; Zhongyan Shan; Weiping Teng (International Journal of Endocrinology)
Estradiol (E2) promotes metastatic propensity. However, the detailed mechanism remains largely unknown. E-cadherin, vimentin, and MMP-9 play a dominant role in the metastatic process. We aimed to investigate the effects of E2 on metastatic potential of PTC cell line BCPAP and on E-cadherin, vimentin, and MMP-9 protein expression. PTC cell line BCPAP was evaluated for the presence of estrogen receptor (ER) by western blot analysis. The effects of E2, PPT (a potent ERα-selective agonist), and DPN (a potent ERβ-selective agonist) on modulation of metastatic phenotype were determined by using in vitro scratch wound assay and invasion assay. In addition, the effects on E-cadherin, vimentin, and matrix metalloproteinase-9 (MMP-9) protein expression were evaluated by Western blot analysis. We found that BCPAP cells expressed ERα and ERβ. E2 and PPT enhanced, but DPN inhibited, the migration and invasion of BCPAP cells in an in vitro experimental model system that is modulated by E-cadherin, vimentin, and MMP-9. These findings indicate that E2 induces the metastatic potential of BCPAP cells through ERα and ERβ. The two ER subtypes play differential roles in modulation of BCPAP cell metastasis and the related molecule expressions including E-cadherin, vimentin, and MMP-9.